IMPLEMENTASI PENETAPAN PAJAK KENDARAAN BERMOTOR UBAH BENTUK PADA SAMSAT KABUPATEN TIMOR TENGAH SELATAN - Emerensye Sofia Yublina Pandie; Febryan Cornelis Lomi; Sebastianus Adi Santoso Mola (J-Icon : Jurnal Komputer dan Informatika, 2019)
The problem in doing the majoring in SAMSAT of sub-province of Timor Tengah Selatan can be solved by using information system. In a month SAMSAT of sub-province of Timor Tengah have served 3.131 taxpayer, that means for a day SAMSAT of sub-province of Timor Tengah served approximately reach 150 taxpayer and total vehicles in registration is 39.492 vehicles. The system that is developed to maintain vehicles data, types of vehicle data, vehicles brands data, dumps data, vehicles price data, registration data, and to count vehicles tax determining rightly dan quickly and can gain the report of all registration data, specific report of the vehicles, specific report of vehicles tax determining and receipt tax payments of vehicles transform. This system capable to answered the hypothesis H0 about contentment of service with satisfaction level more than 70% viz 78%.